This is the key to the kingdom - Allison, Diane Worfolk (Little, Brown, 1992)
In the illustrations accompanying this traditional nursery rhyme, a child finds a key and goes on a magical trip away from her squalid inner-city environment into a landscape filled with color, excitement, and love.